Neck circumference in adolescents and cardiometabolic risk: A sistematic review - Morais,Aisha Aguiar (2018)
Summary Objective: To critically analyze articles on the relation between neck circumference (NC) in adolescents and: body mass index, fat distribution, metabolic syndrome and its individual components, and cardiovascular risk. Method: Systematic review undertaken by two independent researchers using the Pubmed/Medline, Lilacs/Medline, Scielo and Cochrane databases in English, Spanish and Portuguese in the period comprising the past 5 years. Results: Eighteen (18) articles were selected. The articles show an association between NC in adolescents and body fat (BMI), central fat distribution (WC), metabolic syndrome and several of its individual components, and cardiovascular risk. Some values are proposed for NC cutoff points as a diagnostic tool for nutritional status, high blood pressure and pre-hypertension, cardiovascular risk, insulin resistance and metabolic syndrome. We identified a percentile curve constructed for Brazilian adolescents. Conclusion: There is a shortage of studies with representative samples, variety at the NC measurement sites, and the age of the participants, which makes it difficult to establish definitive landmarks.